Inovasi E-Modul Praktikum Variasi Genetik Lalat Buah Lokal Berbasis Project-Based Learning Mapalus dalam Meningkatkan Keterampilan Proses Sains (Lembaga Pengembangan Kinerja Dosen, 2026)
Genetics learning at the junior high school level still faces obstacles due to the lack of interactive practicum media that can help students understand abstract concepts contextually. The use of local fruit flies (Drosophila melanogaster) combined with the Mapalus cultural value is a learning innovation with the potential to improve students' science process skills. This study aims to develop and examine the feasibility and effectiveness of a practicum e-module on the genetic variation of local fruit flies based on Project-Based Learning (PjBL) Mapalus toward the science process skills of grade IX-B students. The study used the Research and Development (R&D) method with the 4D development model (Define, Design, Develop, Disseminate) and a mixed methods approach. The research was conducted at SMP Katolik Stella Maris Tomohon, involving small-group and large-group trials using validation instruments, questionnaires, and achievement tests. The results show: media validation obtained 96.25%, material validation 91.67%, and teacher assessment 91.25%, all in the very feasible category. Student response reached 83.35% in the very good category. The Wilcoxon Signed-Rank Test yielded p = 0.000 (< 0.05), indicating a significant improvement in learning outcomes, with the mean score increasing from 51.36 to 76.36. The N-Gain analysis obtained 0.495 (moderate category), and 16 of 22 students (72.72%) achieved moderate to high improvement.